2019
DOI: 10.11157/anzswj-vol31iss2id637
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ experiences of student feedback: A view from a department of social work in Sweden

Abstract: INTRODUCTION: Course evaluations play a significant part in the facilitating of educational programmes at a university. Along with course evaluations, students are often asked for their reflections on teachers’ pedagogical methods and approaches. These types of questions canbe referred to as student evaluations of teaching, or SETs. Separately, there is growing, yet underdeveloped, interest in understanding the emotional impact the role of being a university lecturer has on the individual teacher. This piece o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Although the teachers are confident that they can respond to student feedback, the challenges of teaching and learning in a university are dynamic, especially in light of the COVID-19 pandemic, which became a global issue in early 2020 (WHO, 2020). COVID-19 greatly disrupted higher education since universities have had to close their doors, stop face-to-face interactions, and rapidly transition teaching, learning, and assessments onto a digital platform (Lemoine & Richardson, 2020;McCormack et al, 2021;Melnyk et al, 2020). Some scholars found that teachers were working under pressure due to the workfrom-home environment, as working from home creates challenges for teachers with familial responsibilities who must manage their time between domestic roles, teaching and researching (Neuwirth et al, 2020;Watermeyer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the teachers are confident that they can respond to student feedback, the challenges of teaching and learning in a university are dynamic, especially in light of the COVID-19 pandemic, which became a global issue in early 2020 (WHO, 2020). COVID-19 greatly disrupted higher education since universities have had to close their doors, stop face-to-face interactions, and rapidly transition teaching, learning, and assessments onto a digital platform (Lemoine & Richardson, 2020;McCormack et al, 2021;Melnyk et al, 2020). Some scholars found that teachers were working under pressure due to the workfrom-home environment, as working from home creates challenges for teachers with familial responsibilities who must manage their time between domestic roles, teaching and researching (Neuwirth et al, 2020;Watermeyer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As COVID-19 affected countries worldwide, fear of the deadly virus necessitated tremendous changes in the educational sector. During this unprecedented time, educators had to transition to online instruction regardless of their willingness or preparedness (Lemoine & Richardson, 2020;McCormack et al, 2021). In this institution, during the early transition to teaching and learning online, many teachers felt anxious and stressed about delivering lessons online and creating teaching materials that support students' learning while away from campus.…”
Section: English Teachers' Perceptions Of the Institution's Role In Implementing Setmentioning
confidence: 99%